2022
DOI: 10.5194/essd-2022-39
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Individual tree point clouds and tree measurements from multi-platform laser scanning in German forests

Abstract: Abstract. Laser scanning from different acquisition platforms enables collecting 3D point clouds from different perspectives and with varying resolutions. Such point clouds allow us to e.g., retrieve information about the forest structure and individual tree properties, or to model individual trees in 3D. We conducted airborne laser scanning (ALS), UAV-borne laser scanning (ULS) and terrestrial laser scanning (TLS) in German mixed forests with species typical for Central Europe. We provide the spatially overla… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Finally, Table 8 represents the quantitative assessment of the FVLS-DL, VLS-DL, and real (geometric only) models on different datasets. In addition to the point clouds created from Weiser et al (2023) (results reported in Tables 4 and 7), the classification performance of the models (Real, VLS-DL and FVLS-DL) was assessed with point clouds from Wang et al (2021), for both the isolated and the near trees case, and for point clouds used in Xi et al…”
Section: Leaf-wood Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, Table 8 represents the quantitative assessment of the FVLS-DL, VLS-DL, and real (geometric only) models on different datasets. In addition to the point clouds created from Weiser et al (2023) (results reported in Tables 4 and 7), the classification performance of the models (Real, VLS-DL and FVLS-DL) was assessed with point clouds from Wang et al (2021), for both the isolated and the near trees case, and for point clouds used in Xi et al…”
Section: Leaf-wood Resultsmentioning
confidence: 99%
“…For the leaf-wood case, synthetic meshes generated with the algorithm by Weber and Penn (1995), and the Wytham Woods 3D model (Calders et al, 2018;Liu et al, 2022) are used. Real labeled point clouds (Hessigheim for the urban case, point clouds from Weiser et al (2023) for the leaf-wood case) serve as training data for the deep learning (DL) models. The performance of the models trained on real data and those trained on virtual data are evaluated and compared quantitatively and qualitatively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…VALIDATION BY LIDAR DATA Finally, we study the uncertainty of trained models on stand level. We utilize a dataset that get assembled from forests in Baden-Württemberg, Germany in the years 2019 and 2020 [27]. It embraces 12 separate plots, each covering a spatial area of about one hectare.…”
Section: Uncertainty Evaluationmentioning
confidence: 99%
“…The analysis of high-resolution aerial imagery in [26] revealed the accuracy of estimated crown diameter significantly varied with plots (0.63 and 0.85) when compared with height estimations. According to [27], the relative error of tree crown diameter derived from airborne/UAV-borne LiDAR data is significantly larger than that of derived tree height (19.22% and 20.7% for crown diameter, 11.70% and 10.97% for tree height estimation respectively). In fact, the crowns of individual trees in e.g.…”
mentioning
confidence: 99%